Socialization and Mentoring of the Results of the Development of Volleyball Game Learning Techniques for Physical Education Teachers - Destri ani; Herri Yusfi; Soleh Solahuddin (Jurnal Dharma Pendidikan dan Keolahragaan, 2021)
Socialization and mentoring of the results of the development of volleyball game learning techniques for Physical Education teachers in Ogan Ilir Regency is carried out with the aim of providing additional knowledge about the results of learning development on big ball material, especially volleyball games, this is done because teachers need to gain knowledge new regarding the results of research activities in learning. The number of participants in this activity was 80 teachers, which was conducted in October 2020. Socialization and mentoring was carried out in several ways or methods, namely by lecturing, question and answer, and mentoring. Based on the results of the evaluation of the socialization and mentoring activities, it shows the level of understanding of the teachers on average is 94.5% and the results of the application of activities in the form of practice of making teaching materials on average are 79.25%, and have entered the good category, so the results This service activity can be used as an alternative teaching material for Physical Education teachers.Keywords: socialization, mentoring, development, learning, volleyball